2021
DOI: 10.3390/biomedicines9080913
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Biological Aging and Underestimation of Subjective Age Are Risk Factors for Severe COVID-19

Abstract: In an epidemic, it is important to have methods for reliable and rapid assessment of risk groups for severe forms of the disease for their priority vaccination and for the application of preventive lockdown measures. The aim of this study was to investigate risk factors for severe forms of COVID-19 in adults using indicators of biological and subjective aging. Longitudinal studies evaluated the severity of the disease and the number of cases. Respondents (447) were divided into “working group” and “risk group”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The most important individual typological features was found to be gender. This is consistent with data previously obtained by us [ 54 , 58 ] and by other researchers [ 59 ]. The present study shows that, both in men and women, different resources are associated with the relative biological aging index.…”
Section: Discussionsupporting
confidence: 94%
“…The most important individual typological features was found to be gender. This is consistent with data previously obtained by us [ 54 , 58 ] and by other researchers [ 59 ]. The present study shows that, both in men and women, different resources are associated with the relative biological aging index.…”
Section: Discussionsupporting
confidence: 94%
“…In this sense, a recent article reported that men have accelerated biological aging during quarantine. Interestingly, this study found that biopsychological age might determine the risk to develop severe COVID-19 [194].…”
Section: Role Of Inflammaging In the Pathogenesis Of Covidmentioning
confidence: 62%
“…These were useful to understand the biological mechanism of aging, however, were inflexible to control the aging process. Moreover, limited studies were conducted to assess the BA as an index for predicting the risk of disease [ 26 , 27 ]. In this study, BA, which is calculated based on self-assessed risk factors, can be a useful indicator of health status.…”
Section: Introductionmentioning
confidence: 99%